Pengembangan Media Pembelajaran Berbasis Video Interaktif Pada Pembelajaran Matematika Materi Pecahan Kelas III Sekolah Dasar - Adhulhadi, Adhulhadi; Manurung , Alberth Supriyanto (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
The research was motivated by the lack of learning media used in the classroom, especially at SDN Pusaka Rakyat 02. Apart from that, teachers have never utilized or used interactive learning media as learning media in the classroom. The research carried out aims to determine the steps taken in developing interactive video-based learning media on fraction material and to determine the level of validity of the media developed in terms of validation results. This research is research and development or Research and Development (R&D) which refers to the ADDIE development model which contains five steps, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects in this research were class V students at SDN Pusaka Rakyat 02 with a total of 15 students. This research data was obtained by observation, interviews and questionnaires. The results of the research show that the interactive video-based learning media that was developed obtained a language expert validation score of 80% with the